Parental Concern about Environmental Chemical Exposures and Children's Urinary Concentrations of Phthalates and Phenols - Pell, Tripler (J Pediatr, 2017)
OBJECTIVES: To examine whether parents' concerns about environmental chemical exposures were associated with urinary phthalate and phenol concentrations in their school-age children. STUDY DESIGN: In a prospective cohort of 218 mother-child pairs from Cincinnati, OH (2010-2014), we measured 11 phthalate metabolites and 5 phenols in urine samples when children were age 8 years and used questionnaire data from caregivers. We estimated the covariate-adjusted percent difference in phthalates and phenols among children of parents who expressed concern about environmental chemical exposures compared with children whose parents did not. RESULTS: Concentrations of four phthalates, bisphenol S (BPS), and bisphenol A (BPA) were lower among children whose parents expressed concern about environmental chemicals (n= 122) compared with those who did not (n=96). Di-2-ethylhexyl phthalate metabolites, BPS, and BPA concentrations were 23% (95% CI:-38, -5), 37% (95% CI:-49, -21), and 13% (95% CI:-26, 3) lower, respectively, among children whose parents expressed concern compared with those whose parents did not. Triclosan concentrations were 35% higher (95% CI:-2, 87) among children whose parents expressed concern compared with children whose parents did not. CONCLUSIONS: Parental concern about environmental chemicals was associated with lower childhood urine concentrations of several phthalates and phenols; unexpectedly, parental concern was associated with higher triclosan concentrations. These results suggest that parental concern may be an important factor in mitigating children's phthalate and phenol exposures.